Changes in Self-Disclosure Behavior Following an Intensive "Encounter" Group Experience - Brasfield, Charles R.; Cubitt, Anne (Canadian Journal of Counselling and Psychotherapy, 2012)
The present research was conducted because of concern for the paucity of studies dealing with behavioral effects of encounter groups, even though such groups are now widely known and frequently described subjectively. From a volunteer pool of seventy-one undergraduate students willing to participate in "encounter group research" for a nominal fee, sixteen (8 male, 8 female) were selected for participation. The selection was based on a clinical interview conducted according to previously established criteria designed to identify and de-select individuals with pressing psychological conflicts. After selection, each student completed two paper-and pencil personality measures and a behavioral measure of self-disclosure. For the behavioral measure of self-disclosure, each student was asked to disclose five items of personal information to a peer stranger of the same sex and, separately, to a peer stranger of the opposite sex. Each student individually selected the self-disclosure items from a list of items provided by the experimenters. Intimacy scores for all self-disclosures were recorded. Four male and four female students were then invited to participate in an encounter group while the other students were asked to delay their group participation until the following semester. At the end of eight weeks (and the encounter group) all sixteen students were again asked to complete the same personality and self-disclosure measures. Pre-post comparisons were computed as well as comparisons between the encounter group and control group students. Results are discussed in terms of clinical and ethical considerations in conducting encounter groups, the format of the particular group, group leadership styles, and clinical aspects of the group process.